Chronic Inflammation Index-Based Tumor Subsite Classification Correlated with Chemotherapy Benefit and Survival Outcomes in Stage II-III Colorectal Cancer - Lu Y; Ye QY; Mei O; Li YN; Peng Y; Ying HQ; Cheng XX (Journal of Inflammation Research)
Ying Lu,1,* Qiu-Ying Ye,1– 3,* Ou Mei,4,* Ya-Nan Li,1 Yue Peng,1 Hou-Qun Ying,1,3,5 Xue-Xin Cheng1 1Department of Clinical Laboratory, The Second Affiliated Hospital, Jiangxi Medical College, Nanchang University, Nanchang, 330006, People’s Republic of China; 2Department of Medical Technology, Jiangxi Medical College, Shangrao, 334000, People’s Republic of China; 3Department of Laboratory Medicine, Central Hospital of Shangrao City, Shangrao, 334000, People’s Republic of China; 4Department of Orthopedics, Affiliated Hospital of Jiangxi University of Traditional Chinese Medicine, Nanchang, 330006, People’s Republic of China; 5Shangrao Medical Center, The Second Affiliated Hospital of Nanchang University, Shangrao, 334000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xue-Xin Cheng, Department of Clinical Laboratory, Immunity and Inflammation Key Laboratory of Jiangxi Province, The Second Affiliated Hospital of Nanchang University, No. 1 of Minde Road, Nanchang, 330006, People’s Republic of China, Tel/Fax +86 0791-86297662, Email cxxncu@163.com Hou-Qun Ying, Department of Clinical Laboratory, Immunity and Inflammation Key Laboratory of Jiangxi Province, The Second Affiliated Hospital of Nanchang University, No. 1 of Minde Road, Nanchang, 330006, People’s Republic of China, Tel/Fax +86 0791-86297662, Email yinghouqun2013@163.comPurpose: This study aimed to develop and validate an integrated inflammatory prognostic index and to investigate associations between primary tumor location, chronic inflammatory status, adjuvant chemotherapy response, and survival outcomes in stage II–III colorectal cancer (CRC).Patients and Methods: A total of 1413 stage II–III CRC patients who underwent radical resection were enrolled and divided into discovery and validation cohorts. Preoperative systemic inflammatory biomarkers were quantified, and patients were followed for 3 years to establish an optimal chronic inflammatory index (CII) and evaluate its association with survival and chemotherapy efficacy across primary tumor locations.Results: The comprehensive CII was the top-performing prognostic biomarker, with time-dependent AUCs of 0.71(95% CI: 0.68– 0.74) for 36-month RFS and 0.74(95% CI: 0.70– 0.77) for OS. Furthermore, the 3C (CII, CEA and CA19-9) combined score demonstrated prognostic predictive AUCs of 0.74(95% CI: 0.71– 0.77) for RFS and 0.76(95% CI: 0.72– 0.79) for OS in the overall population. The splenic flexure and ascending colon showed significantly elevated CII levels versus other subsites, and the disease was divided into the proximal colon, transverse colon, distal colon and rectum. A significant CII gradient emerged across subsites (proximal > transverse > distal > rectal), with corresponding survival decrements (log-rank p < 0.001). Proximal CRC exhibited marked worse survival outcomes (p = 0.002 for RFS and p = 0.001 for OS) and inferior chemotherapy efficacy (p < 0.001 for RFS and OS) versus rectal cancer, with no significant differences between adjacent subsites (all p > 0.05).Conclusion: The validated CII represents a biologically relevant, subsite-specific prognostic biomarker in CRC. The chronic inflammation-based tumor subsite classification correlated with chemotherapy efficacy and clinical outcomes, highlighting its potential for personalized treatment strategies.Keywords: colorectal cancer, systemic inflammation, location-based therapy, precision medicine